Interference in the Activities of Government Authorities: Peculiarities of Situation - Popov, Volodymyr (Archives of Criminology and Forensic Sciences, 2024)
During the investigation of any criminal offense, it is essential to clarify and substantiate key details about the event, such as the location, time, manner, etc. Among these, details regarding the circumstances surrounding criminal offense commission hold particular importance, as they are pivotal in determining the investigative (search) algorithms and procedural actions that need to be taken to ensure the resolution of tactical investigation tasks. The issue of situation during interference in the activities of government authorities is no exception. In light of the above, the Article Purpose is defined as figuring out the place of situation in the activities of government authorities within forensic characterization, determining its inherent components and specific characteristics. The results of scientific research have revealed that circumstances of a criminal offense are an essential element of forensic characterization of criminal offenses related to interference in the activities of government authorities, which includes information regarding the time and place of these.